Landslide hazard mapping using limit equilibrium method with GIS application of roadway traversing mountain slopes: The case of Kitaotao Bukidnon, Philippines (Journal of Nepal Geological Society, 2018)
The national highway section of the Municipality of Kitaotao along the Davao City route plays a vital role in the transport of goods and services in the region. However, this national highway is prone to rainfall-induced landslides. Records show that almost every year this highway is being disrupted by landslide and road clearing operations would take several hours or even up to several days. This study aimed to improve the present landslide hazard map using Limit Equilibrium Method (LEM) and GIS techniques in order to present the spatial distribution of Factor of Safety (FS) in the area. A LEM based software (SLOPE /W) was utilized in the present study and Bishop Simplified slope stability model was adopted in calculating the FS. Geotechnical properties like cohesion, friction angle and unit weight were used in the analyses. The soil thickness data gathered were correlated to the slope angle in order to determine the spatial distribution of soil thickness in the area. The LHZM revealed that areas with low to very low stability are extensively found in the southern part and some areas in the northern portion. The accuracy of the model was validated through actual field observations and also by overlying the landslide inventory over the LHZM. It was found that 77.80 % of inventoried landslides are in low to very low stability zones. The present study adapts a deterministic approach using LEM of slope stability analysis and clusters the hazard zonation in terms of the spatial variation of FS in every 20 m x 20 m slope area employing GIS techniques; hence, this provides better insight on the landslide susceptibility throughout the study area and can be used directly for engineering design purposes.